Flexible parametric multistate modelling of employment history. (June 2019) - Hout, Ardo van den; Tan, Wenhui
Abstract: A multistate model is used to describe employment history. Transition-specific rates are defined using generalized gamma distributions and Gompertz distributions. This flexible parametric modelling of the rate of change is combined with latent classes for unobserved propensity to change jobs. The propensity is described by two latent classes which can be interpreted as consisting of movers and stayers . The modelling is illustrated by analysing longitudinal data from the German Life History Study.